Hydro-meteorological flood simulation integrating radar rainfall with infoworks RS™ and GIS analysis / Zaizatul Zafflina Mohd Zaki, Wardah Tahir and Zuraisah Dollah - Mohd Zaki, Zaizatul Zafflina; Tahir, Wardah; Dollah, Zuraisah (Research Management Institute (RMI), 2011)
Thunderstorms and incessant monsoon rainfalls are the cause of many natural disasters including floods in Malaysia. The damages and losses due to floods are so immense that billions of ringgit has been spent for salvages and recoveries. Even though the government has provided various flood mitigation measures but flooding still occur frequently especially if the systems related are not designed properly. A non structural measure strategy is proposed to help to reduce these damages. Identification of flood prone areas would assist the relevant agencies in issuing a timely warning to victims in the affecting areas. In addition, for an integrated flood monitoring measure, the use of alternative rainfall measurement system such as weather radar is considered crucial to complement areas inaccessible to rain-gauges. In addition, by using develop model flood occurrence can be monitored more closely.